The role of impact on the meaning of generic sentences - Mirabile, Patricia; van Rooij, Robert; Schulz, Katrin (Frontiers in Psychology, 2024)
Generic sentences (e.g. "Dogs bark") express generalizations about groups or individuals. Accounting for the meaning of generic sentences has been proven challenging, and there is still a very lively debate about which factors matter for whether or not we a willing to endorse a particular generic sentence. In this paper we study the effect of {\it impact} on the assertability of generic sentences, \rewritek{where impact refers to the dangerousity of the property the generic is ascribing to a group or individual}. We run three preregistered experiments, (one of which doubled as a replication of Cimpian et al., 2010a) testing assertability and endorsement of novel generic sentences with visual and textual stimuli. Employing Bayesian statistics} we found that impact influences the assertability, and endorsement, of generic statements. However, we observed that the size of the effect impact value may have been previously overestimated by theoretical and experimental works alike. We also run an additional} descriptive survey testing standard examples from the linguistic literature and found that at least for some of the examples endorsement appears to be lower than assumed. We end with exploring possible explanations for our results.}